The effect of calcination conditions on oat husk ash pozzolanic activity. (2022) - Bonifacio, A.L.; Archbold, P.
Abstract: Supplementary cementitious materials (SCMs) are known and used to reduce cement consumption, but some waste sources currently used for partial cement replacement are threatened by changing industrial production processes and local availability. Thus, considering possible sources of amorphous silica for use as SCM, especially pozzolans, there is an opportunity to investigate the use of agricultural residues such as oat husks, which currently have little or no commercial value. This work aims (i) to identify the burning temperature that promotes the reduction of carbon content and increase the amorphous material, (ii) to present the chemical and physical characterization analysis results, and (iii) to evaluate the pozzolanic potential of selected oats husks ashes (OHA) produced under controlled calcination temperatures. Local samples of oat husks were sun-dried, sieved, and split into two portions. One portion was subjected to analysis of moisture content, and the second portion was pre-calcined at 350 °C for 2 h in an aerated laboratory oven and turned into ashes under 400 to 700 °C respectively, using ramp heating rate of 10 °C/min. The ashes were ground in a ball mill and subjected to chemical and physical analysis, considering Loss on Ignition (LOI) at 950 °C, chemical composition through Energy Dispersive X-Ray Analysis (EDX), structural state analysis by X-ray diffraction (XRD), morphology by digital microscopy, density using glass pycnometer and chemical reactivity with calcium hydroxide measured through thermogravimetric analysis of a control mortar defined as (R 3 ) model paste. The results show that the ash chosen for pozzolanic potential analysis, produced at 600 °C, shows an average ash content value of 3.6%, and chemical concentration of 45.97% oxygen (O), 21.2% silicon (Si), and 16.91% potassium (P), in addition to evidence that characterizes crystallization of its structure and consumption of 8.74% of Ca(OH)2 from the control matrix, indicating low pozzolanic activity. It was concluded that local oat husks in Ireland calcinated between 600 and 700 °C presented a favorable balance between the percentage of residual carbon amount and silica in the amorphous form that is favorable to react with calcium hydroxide forming calcium silicate hydrate. It opens up a possibility of investigating the use of OHA as SCM, requiring more studies about the oats husks calcination time, cement replacement rate, and performance tests to consider practical applications, and maybe contributing to reducing the OPC consumption, production necessity, and consequently, the environmental issue caused by its production.